2018
DOI: 10.1186/s12874-018-0578-7
|View full text |Cite
|
Sign up to set email alerts
|

Mediation analysis with a time-to-event outcome: a review of use and reporting in healthcare research

Abstract: BackgroundMediation analysis tests whether the relationship between two variables is explained by a third intermediate variable. We sought to describe the usage and reporting of mediation analysis with time-to-event outcomes in published healthcare research.MethodsA systematic search of Medline, Embase, and Web of Science was executed in December 2016 to identify applications of mediation analysis to healthcare research involving a clinically relevant time-to-event outcome. We summarized usage over time and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
82
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(84 citation statements)
references
References 42 publications
2
82
0
Order By: Relevance
“…[81,82]. Our findings and those of others [78,80] suggest that existing guidelines such as the CONSORT for randomised controlled trials or STROBE for observational studies do not cover the…”
Section: Accepted Manuscriptmentioning
confidence: 61%
See 3 more Smart Citations
“…[81,82]. Our findings and those of others [78,80] suggest that existing guidelines such as the CONSORT for randomised controlled trials or STROBE for observational studies do not cover the…”
Section: Accepted Manuscriptmentioning
confidence: 61%
“…One-third of the systematic reviews reported limitations in synthesising primary mediation studies due to inadequate reporting. Most often, these reviews identified that the primary studies reported insufficient detail about the statistical analysis and did not report key to-event healthcare research was varied and suboptimal, and highlighted the need for formal guidance to improve reporting standards [78,80].…”
Section: Reporting Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several authors have discouraged the use of the Cox PH model for traditional mediation analysis (Lange & Hansen, 2011;Lapointe-Shaw et al, 2018;Martinussen, Vansteelandt, Gerster, & Hjelmborg, 2011;VanderWeele, 2011) because the product and difference methods yield different indirect effect estimates when based on the Cox PH model (Gelfand et al, 2016;Tein & MacKinnon, 2003). These two methods are assumed to approximate each other only in case of rare outcomes (VanderWeele, 2011).…”
Section: Figure 1 Single Mediator Modelmentioning
confidence: 99%